Improving HPV Vaccine Coverage in Tennessee: Addressing Barriers and Expanding Access for Mid-Adults - Donald J. Alcendor; Patricia Matthews-Juarez; Mohammad Tabatabai; Derek Wilus; James E. K. Hildreth; Paul D. Juarez (Pathogens)
Human papillomavirus (HPV) is the most common sexually transmitted infection in the US and the world. Infection with high-risk oncogenic HPV strains has been shown to induce cellular transformation leading to anogenital and oropharyngeal cancers. The HPV vaccine, first developed in 2006 for females aged 9–26 years, has been demonstrated to be safe and effective in preventing 90% of all HPV-associated cancers. However, vaccine hesitancy, misinformation, and barriers to vaccine access has resulted in suboptimal vaccination rates among adolescent populations, especially in rural communities in the South. HPV vaccine coverage in Tennessee is currently below the national average and below the Healthy People 2030 goal of an 80% vaccination rate for individuals 13–17 years old based on recommendation guidelines for up-to-date HPV vaccination status as of 2022. HPV vaccination rates for Tennesseans with private insurance in 2022 were 68% and 38% for those that were uninsured. Up-to-date HPV vaccination rates in 2022 for Tennesseans were 58% and 46% for those living in urban communities and rural communities, respectively. Overall, HPV-associated cancers rates are higher in Tennessee, at 12.9/100,000 compared to the overall rate in the US of 11.8/100,000 persons in 2022. Interventions to improve HPV vaccine awareness, education, and access could improve vaccine confidence and uptake, especially among rural and uninsured populations in Tennessee. Most recently, the Advisory Committee on Immunization Practices (ACIP) expanded recommendations for HPV vaccinations for some individuals aged 27–45 years who were not vaccinated at a younger age, with shared clinical decision making. Further research is needed to evaluate the impact of this recommendation on HPV vaccination rates and cancer prevention in Tennessee.